Laws of Ice Deformation (Zakonomernosti Deformirovaniya Lda) - Vyalov,S. S. (1970)
The study of ice deformations laws was performed in a specially equipped laboratory constructed in a snow stratum to maintain a fairly constant below-zero temperature. The following studies were performed. Compression of ice without lateral expansion to model the contraction process of the ice stratum. Compression of ice with lateral expansion to model the free spreading of the ice column under its own weight (substituted by an external load). Ice dislocation under plane parallel deformation (between two parallel toothed plates) to model ice flow under displacement forces. Ice shear (with Maslov's shear instrument) under the action of tangential and perpendicular forces to model ice bed motion under simultaneous action of flow forces and its own weight. Ice hardness by ball probe measurements (N. A. Tsitovich's method). (Author) Trans. of Sovetskaya Antarkticheskaya Ekspeditsiya, 1955- (USSR) v10 p239-249 1960.